Zyxin protects from hypertension-induced cardiac dysfunction - Al-Hasani, Jaafar; Sens-Albert, Carla; Ghosh, Subhajit; Trogisch, Felix; Nahar, Taslima; Friede, Prisca Amayi Patricia; Reil, Jan-Christian; Hecker, Markus (Cellular and molecular life sciences, 2022)
Arterial hypertension causes left ventricular hypertrophy leading to dilated cardiomyopathy. Following compensatory cardiomyocyte hypertrophy, cardiac dysfunction develops due to loss of cardiomyocytes preceded or paralleled by cardiac fibrosis. Zyxin acts as a mechanotransducer in vascular cells that may promote cardiomyocyte survival. Here, we analyzed cardiac function during experimental hypertension in zyxin knockout (KO) mice. In zyxin KO mice, made hypertensive by way of deoxycorticosterone acetate (DOCA)-salt treatment telemetry recording showed an attenuated rise in systolic blood pressure. Echocardiography indicated a systolic dysfunction, and isolated working heart measurements showed a decrease in systolic elastance. Hearts from hypertensive zyxin KO mice revealed increased apoptosis, fibrosis and an upregulation of active focal adhesion kinase as well as of integrins α5 and β1. Both interstitial and perivascular fibrosis were even more pronounced in zyxin KO mice exposed to angiotensin II instead of DOCA-salt. Stretched microvascular endothelial cells may release collagen 1α2 and TGF-β, which is characteristic for the transition to an intermediate mesenchymal phenotype, and thus spur the transformation of cardiac fibroblasts to myofibroblasts resulting in excessive scar tissue formation in the heart of hypertensive zyxin KO mice. While zyxin KO mice per se do not reveal a cardiac phenotype, this is unmasked upon induction of hypertension and owing to enhanced cardiomyocyte apoptosis and excessive fibrosis causes cardiac dysfunction. Zyxin may thus be important for the maintenance of cardiac function in spite of hypertension.